SOCIOLINGUISTIC PROFILE RESERCH PAPER: COMPUTER PROGRAMMING STUDENTS AT TASHKENT PEDAGOGICAL TECHNICAL. - Kdirbayeva Sevara Berdimuratovna (TADQIQOTLAR, 2026)
Annotation: This paper presents a sociolinguistic profile of Group 102, a class of 14 first-year Computer Programming students at Tashkent Pedagogical Technical (TPT) in Uzbekistan. The profile examines learner backgrounds across three dimensions — regional origin, gender, and ethnic and linguistic identity — and situates these within the multilingual context of Tashkent and the English-using futures for which students are being prepared. Drawing on frameworks from World Englishes, Global Englishes, raciolinguistic theory, standard language ideology, and translanguaging, the paper identifies two overlapping subgroups whose differential access to English creates meaningful instructional challenges. Pedagogical implications address differentiated instruction, the strategic use of translanguaging, and the disruption of standard language ideologies that disadvantage regional, multilingual, and female learners. Assessment implications focus on analytic rubric design, the risks of raciolinguistic bias in evaluation, and advocacy for contextually appropriate assessment in English for Specific Purposes (ESP) settings.